Tribbles homolog 2 promotes hepatic fibrosis and hepatocarcinogenesis through phosphatase 1A‐Mediated stabilization of yes‐associated protein. (10th January 2021) - Xiang, Dejuan; Zhu, Xiaoyun; Zhang, Yanqiu; Zou, Jie; Li, Jie; Kong, Lingyi; Zhang, Hao
Abstract: Background & Aims: Hepatic stellate cells (HSCs) play critical roles in liver fibrosis and hepatocellular carcinoma (HCC). Tribbles homolog 2 (TRIB2) is an oncogene implicated in a variety of cancers, including liver cancer. However, the biological function and regulatory mechanism of TRIB2 in HSCs are poorly understood. In addition, little is known about its role in liver fibrosis progression to HCC. Here, we revealed the clinical significance of TRIB2 in liver fibrosis and HCC development. Methods: We investigated TRIB2 promoting liver fibrosis in vitro and in vivo. In mouse model of liver fibrosis and HCC, we measured hepatic fibrosis and HCC level through knockdown TRIB2 with shRNA. In addition, we performed western blotting, real‐time quantitative PCR, immunofluorescence and co‐immunoprecipitation assay to study TRIB2 function in LX‐2 cells. Results: TRIB2 expression was strongly upregulated in human fibrotic liver tissues and HCC tissues. TRIB2 colocalized with α‐smooth muscle actin (α‐SMA) in fibrotic and HCC liver tissues. Knockdown of TRIB2 inhibited HSC activation and liver fibrosis in vitro and in vivo. TRIB2 promoted Yes‐associated protein (YAP) stabilization, nuclear localization, and subsequent fibrotic gene expression independent of the MST‐LATS phosphorylation cascade in HSCs. TRIB2 interacted with YAP to recruit phosphatase 1A (PP1A), promoting PP1A‐mediated YAP dephosphorylation. TRIB2 knockdown potently attenuated the development of fibrosis‐associated liver cancer. Conclusions: TRIB2 is an attractive target for hepatic fibrosis and fibrosis‐associated liver cancer treatment.